Analisis Prediksi Kegagalan Keuangan Menggunakan Model Altman, Wang dan Campbell dan Springate pada Perusahaan yang Delisting dari Bursa Efek Indonesia Periode 2009-2012 - , DANASTRI RARAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to test whether prediction model analysis of Altmanâs, Wang and Campbellâs, and Springateâs can be used to predict precisely which company is delisted from Indonesia Stock Exchange (IDX) due to financial distress. The sample of this research are every company that has been delisted forcefully due to financial distress. Those samples will be compared with ten other companies that are listed in the same industry and have the similar value of assets. Furthermore, those companies that have been delisted before will be compared with every company that are listed in the same industry. After being identified, every information about the companies that have been delisted forcefully from IDX will be calculated using Altmanâs, Wang and Campbellâs, and Springateâs formula to specify its cut off. The prediction results of those models will be compared with the actual condition using chi-square. Each of Altmanâs model, Wang and Campbellâs model, and also Springateâs model show significant results to predict the company that has been delisted due to financial distress. The result of this research can be a reference to enrich readerâs knowledge related to prediction of financial distress, also to give useful information that those prediction models can be used in Indonesia.